Inflammatory Biomarkers for Outcome Prediction in Patients With Metastatic Testicular Cancer - Bleve, Sara; Cursano, Maria Concetta; Casadei, Chiara; Schepisi, Giuseppe; Menna, Cecilia; Urbini, Milena; Gianni, Caterina; De Padova, Silvia; Filograna, Alessia; Gallà, Valentina; Rosti, Giovanni; Barone, Domenico; et al. (Frontiers in Oncology, 2022)
Germ cell tumors are the most common malignant tumors in male young adults. Platinum-based chemotherapy has dramatically improved the outcome of metastatic germ cell tumor patients and overall cure rates now exceed 80%. The choice of medical treatment can be guided by the prognosis estimation which is an important step during the decision-making process. IGCCCG classification plays a pivotal role in the management of advanced diseases. However, histological and clinical parameters are the available factors that condition the prognosis, but they do not reflect the tumor molecular and pathological features and do not predict who will respond to chemotherapy. After first line chemotherapy 20-30% of patients relapse and for these patients the issue of prognostic factors is far more complex. Validate biomarkers and a molecular selection of patients that reflect the pathogenesis are highly need. The association between cancer-related systemic inflammation , tumorigenesis and cancer progression has been demonstrated. In the last years, several studies have shown the prognostic utility of immune-inflammation indexes in different tumor types. This review analyzed the prognostic impact of inflammatory markers retrieved from routine blood sands in GCT patients.